2021
DOI: 10.24251/hicss.2021.147
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Use Intention of Digital Wellness Technologies and Its Antecedents Over Time: The Use of Physical Activity Logger Applications Among Young Elderly in Finland

Abstract: Physical inactivity has become a prevalent problem among elderly people. Although digital wellness technologies have been proposed as one promising solution to it, our understanding on the antecedents of the acceptance and use of these technologies among elderly people remains limited. In this study, our objective is to promote this understanding by examining the potential changes in the use intention of digital wellness technologies and its antecedents over time in the case of the young elderly segment and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This is actually in our future plans. Further, as longitudinal research on related topics is much called for, our plan is also to continue the follow-up surveys in order to complement earlier study findings [e.g., [52][53][54].…”
Section: Limitation and Future Researchmentioning
confidence: 99%
“…This is actually in our future plans. Further, as longitudinal research on related topics is much called for, our plan is also to continue the follow-up surveys in order to complement earlier study findings [e.g., [52][53][54].…”
Section: Limitation and Future Researchmentioning
confidence: 99%
“…In this study, we examined the potential longer-term temporal changes in the use intention of digital wellness technologies and its antecedents in the case of the young elderly segment and physical activity logger applications. In comparison to our two prior studies (Makkonen et al, , 2021, we made three main findings. First, we found that our research model continued to perform very well in explaining use intention also after about 18 months of using the application by being able to explain about 83% of its variance at T3 as well as having acceptable reliability and validity at both construct and indicator levels.…”
Section: Discussionmentioning
confidence: 87%
“…The continued use of digital wellness technologies specifically by elderly or young elderly consumers has not been studied much. In [32], utilizing a smaller sample of the data used in the study at hand, the researchers studied continued use over an 18-month period, and found through PLS-SEM that UTAUT2 explains use intention well. The effects of hedonic motivation and habit emerged as significant, whereas the effect of social influence was not.…”
Section: Literature Review and Propositionsmentioning
confidence: 99%